GAMBARAN FAKTOR PENYEBAB MENJADI WANITA PEKERJA SEKS DI HOTSPOT PASEH – TOMO SUMEDANG - Upus Piatun khodijah (Jurnal Ilmiah Bidan (JIB), 2020)
Sex workers is one society diseases that has been known long time ago and is difficult to stop. Based on Paseh Healthcare Centre data in 2015, there are 59 sex workers. Meanwhile, Tomo Healthcare center says that there are 34 sex workers in 2016. Moreover, there are 15 sex workers until June 2017. This research aims to figure out sluttish women causative factors in Paseh – Tomo lounge, Sumedang regency in the year of 2017. This research uses descriptive research. Furthermore, the population and sample of this research are all women in Sumedang regency in 2017 in unknown numbers. This research, moreover, uses accidental sampling as the sampling technique. The instrument of the research is questionnaire. The analysis of this research is univariate analysis using frequency distribution. The result of the research showed that most of sluttish women are in the age of 26 -35 years old (early adolescent) in the amount of 56 people (56,0%). Most of sluttish women with > 1 children are in the amount of 59 people (59,0%). Most of divorced sluttish women are in the amount of 82 people (82,0%). Most of knowledgeable sluttish women are in the amount of 76 people (76,0%). Most of Junior High School educated sluttish women are in the amount of 56 people (56,0%). Most of unemployment sluttish women are in the amount of 99 people (99,0%). Most of poor sluttish women are in the amount of 61 people (61,0%) in Paseh – Tomo lounge, Sumedang regency in the year of 2017. It is expected that Sumedang regency governmental and social services collaborate with other sectoral in nurturing sluttish women by giving additional activities such as religious activities, skill education, and art, as well as giving loan to middle – low society. Sluttish women, furthermore, are expected to find alternative occupation and increasing individual skill such as sewing, weaving, and producing home industries.